The role of gender as a moderator in the relationship between diseaseperception and coping with stress strategies among psychiatric patients - Kłak, Marta; Ozga, Wioletta Karina (Current Problems of Psychiatry, 2025)
Introduction. The perception of disease depends on the patient’s beliefs related to the nature of the illness, the previous personal or family experiences and his/her attitude to them. Patients try to understand and cope with health problems. The purpose of the present study was to answer the question which components of the relationship between the strategies for coping with stress and mental disease perception are moderated by gender. Material and Methods. The study involved 98 patients with depressive disorders, anxiety disorders, schizophrenia, alcohol related disorders. The research of the variables was carried out using the COPE Inventory and Disease Perception Questionnaire. Results. It has been noticed that in men, when their perception of the mental disorder as beneficial increases, the religious strategies for coping with stress become more frequent. Furthermore, the opposite sex pattern emerged. In the situation when an individual’s perception of the illness as a threat increased, female patients less frequently employed religious coping and planning. Furthermore, in women, when the perception of the mental disease as a weakness increases, the frequency of using emotional social support and acceptance decreases. Conclusions. The result indicated that there are opposite patterns of gender specific coping strategy dependent on the mental illness perception.